Evaluation of "How To Be A Good Mentoring Training” Effectiveness for Peer Mentor - Repi, Andhika Alexander (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2020)
"Kakak Pendamping, Support Class Program" is a term for peer mentor of Faculty Psychology WM University program. The mentor needs to be equipped with the knowledge, skills, and attitudes of becoming good mentors through training programs called "How To Be a Good Mentor" training. But, this program hasn’t evaluated whether the training is effective or not. If a training program is not assessed, it will cause several losses for both mentors and the organization. This study aims to identify the effectiveness of the training "How To Be a Good Mentor.” The method used is mix-method and involves all stakeholders in the UKWMS Psychology Faculty, namely staff, students, and Mentors. The results of the study found that "How To Be a Good Mentor" training has not been effective because it does not go through the ideal design stage of training. Without any needs analysis program, and the absence of a training evaluation program, as an action plan due to ineffectiveness of the training that has been held. A training module will be redesigned to develop a training module, "Creating a Full Heart Mentor." This training aims to improve the knowledge, skills, and attitudes of the Mentors. Evaluation of the "Creating a Full Heart Mentor" training is useful in evaluating the results of assessments showing the satisfaction of Mentor to the training process, and improving learning after obtaining training materials. The training on "Creating a Full Heart Mentor" produces needs analysis data used as a further development program for Mentors. "Kakak Pendamping Support Class Program" adalah sebutan untuk peer mentor program Fakultas Psikologi WM University. Sebagai upaya untuk mengoptimalkan program ini, para mentor perlu dibekali dengan pengetahuan, keterampilan, dan sikap bagaimana menjadi mentor yang baik melalui program pelatihan yang dinamakan pelatihan “How To Be a Good Mentor”. Namun program ini belum dievaluasi apakah pelatihan tersebut efektif atau tidak. Jika program pelatihan tidak dievaluasi, maka akan menimbulkan sejumlah kerugian baik bagi mentor maupun organisasi. Penelitian ini bertujuan untuk mengetahui efektivitas pelatihan "How To Be a Good Mentor". Metode yang digunakan adalah mix-method dan melibatkan seluruh stakeholder di Fakultas Psikologi UKWMS yaitu staf, mahasiswa, dan Mentor. Hasil penelitian menemukan bahwa pelatihan "How To Be a Good Mentor" belum efektif karena tidak melalui tahap desain pelatihan yang ideal, tanpa adanya program analisis kebutuhan, dan tidak adanya program evaluasi pelatihan. Sebagai sebuah action plan akibat tidak efektifnya pelatihan yang telah dilaksanakan, maka modul pelatihan akan didesain ulang dan menghasilkan pengembangan modul pelatihan “Menciptakan Mentor Sepenuh Hati”. Pelatihan ini bertujuan untuk meningkatkan pengetahuan, keterampilan, dan sikap para Mentor. Evaluasi pelatihan “Menciptakan Mentor Sepenuh Hati” efektif ditinjau dari hasil evaluasi yang menunjukkan kepuasan pendamping terhadap proses pelatihan, dan peningkatan pembelajaran setelah mendapatkan materi pelatihan. Pelatihan “Membuat Mentor Sepenuh Hati” menghasilkan data analisis kebutuhan yang nantinya akan digunakan sebagai program pengembangan lebih lanjut bagi Mentor.